SÍDÍQ ShAYÍR DÓRETIWSHILIGIN OQÍTÍW USÍLLARÍ - Davletov, B.A. (SCIENCE and SOCIETY, 2023)
The article highlights the issues of teaching Sidik’s creativity as a poet. The research and teaching of the poet’s work was studied using the Cinquain and Interview methods. The examples show the effectiveness of using interactive methods in teaching the creative path of a poet.